Creative Industry And Opportunity In Export Market - Purnamawati, I Gusti Ayu; Herliyani, Elly; Eka Agustini, Dewa Ayu (International Journal of Social Science and Business, 2019)
The important role of MSMEs being the largest business sector in its contribution to the national development is also providing the opportunity of considerable job vacancies. Creative Industry can be one of the alternatives in facing the tight competition of the world market, so that the Government have the obligation to find, support the regional potency and create the strategy of creative industry development in order to compete with  other regions and other countries. Local Economic Development focuses on endogenous development policy utilizing the potential of local human, institutional and physical resources. Whatever form of policy is taken, LED has one goal, which is increasing the number and variety of job opportunities available to the local population.